2022
DOI: 10.1007/s41978-022-00108-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex Clubs in the UK: Recreational Sex, Erotic Diversity and Geographies of Desire

Abstract: Current research has suggested that sex, sexual practices and sexual identities are increasingly being folded into people’s leisure and recreational activities. One area that has witnessed growing popularity has been sex clubs that market themselves as places that enable heterosexual casual, anonymous sexual encounters. Traditionally called swingers’ clubs, these are not strip clubs, lap dancing clubs or brothels, we have very little information about sex clubs or the people who visit them. In response, this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 65 publications
1
8
1
Order By: Relevance
“…A large-scale national survey that examined Australian secondary school students’ choices for contraception and STIs prevention showed condom was the choice contraception method among participants [ 15 ]. This finding is supported by a more recent study among a sample of predominantly young women in Australia1 [ 6 ] and by another study among a general Australian sample [ 14 ]. Watson et al reported the use of dual contraceptive methods; which involve condoms and other contraceptives such as pills [ 16 ].…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…A large-scale national survey that examined Australian secondary school students’ choices for contraception and STIs prevention showed condom was the choice contraception method among participants [ 15 ]. This finding is supported by a more recent study among a sample of predominantly young women in Australia1 [ 6 ] and by another study among a general Australian sample [ 14 ]. Watson et al reported the use of dual contraceptive methods; which involve condoms and other contraceptives such as pills [ 16 ].…”
Section: Introductionsupporting
confidence: 73%
“…Both abstinence and partner fidelity could be described as indicators of the more restrictive conservative norms around young people’s sexuality. Therefore, with greater acculturation to the more liberal and less restrictive sexual norms in Western societies [ 5 , 6 , 11 ], abstinence and partner fidelity may become weakened, while casual sex may become more attractive [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Writing about swingers was another challenge we faced, not only because swingers' sexual, perhaps objectifying language and sexual practices may be shocking as well as uninteresting for the readers, but also because excluding these descriptions completely would disappoint the members of this community. The struggle to write about the swinger world appropriately would mean that ethnographers must consider topics relevant to swingers, while also toning down the explicit language and descriptions for the readers who may feel uncomfortable (see also Haywood, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…This raised questions about who was and was not a swinger and I found that there was a considerable number of people who practiced sex with multiple partners without sharing their partner or without having a partner, as well as people who practiced BDSM; people with polyamorous tendencies without being polyamorous and people in open relationships. The ambiguity of self-identification and this distance in positioning may work as an advantage in swinger research, due to our observation that swinger clubs, like sex clubs (Haywood, 2022a), may facilitate a variety of sexualities and relationship forms.…”
Section: Ethnographer's Positionalitymentioning
confidence: 99%